Animal adventures 3D - Klutho, David E. (New York : Time for Kids Books, 2015)
Featuring 100 large-scale, action photos of wild animals in their natural habitats,Animals Adventures 3D is a one-of-a-kind reading experience. TIME for Kids and master 3D photographer David Klutho present incredible photos, taken only with a 3D camera, along with fascinating facts about Komodo dragons, polar bears, camels, anteaters and more amazing animals. Accompanied by two sets of 3D glasses, this dynamic visual collection of some of the planet's diverse animal life will entertain and educate any animal fan.
"An in your face 3D experience"--Cover.
Primary
Keywords: Animals -- Juvenile literature; Animals; Juvenile works